Workforce issues: the blurring of boundaries in surgical care. (8th April 2021) - Russell, Bradley; Fletcher, Nicholas
Abstract : Bradley Russell and Nicholas Fletcher discuss the need for clear boundaries for those nurses practising at an advanced level in surgical specialties